2019
DOI: 10.1111/tbj.13696
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐negative breast cancer—Role of immunology: A systemic review

Abstract: Breast J. 2020;26:995-999. wileyonlinelibrary.com/journal/tbj | 995

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…To examine whether MATR3 expression is correlated with the aggressiveness and poor prognosis of breast cancer, we compared its expression between triple-negative breast cancer (TNBC) and BLBC and other breast cancer subtypes. TNBC and BLBC represent ~ 15-20% of all breast cancer cases and are generally considered highly aggressive and metastatic [24,25]. RNA-sequencing dataset analysis [26,27] demonstrated that MATR3 expression was significantly lower in the TNBC & BLBC compared to the other subtypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether MATR3 expression is correlated with the aggressiveness and poor prognosis of breast cancer, we compared its expression between triple-negative breast cancer (TNBC) and BLBC and other breast cancer subtypes. TNBC and BLBC represent ~ 15-20% of all breast cancer cases and are generally considered highly aggressive and metastatic [24,25]. RNA-sequencing dataset analysis [26,27] demonstrated that MATR3 expression was significantly lower in the TNBC & BLBC compared to the other subtypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TIL levels are higher in highly proliferating tumors, including human epidermal growth factor receptor 2 (HER2)-positive and TNBC (3). TILs have a strong prognostic and predictive significance, and high TIL levels are positively correlated with pathological complete response rate and patient survival rate (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a prevalent malignancy in female globally, with ~ 1.4 million new cases diagnosed annually [ 1 ], of which triple‐negative breast cancer (TNBC) represents approximately 15–20% and have the highest genomic instability rates when compared with other breast cancer subtypes [ 2 ]. Previous studies have shown that TNBC can stimulate the immune system to form a tumor microenvironment (TME) where immune cells are the main component which can be identified as potential prognostic factors for TNBC patients [ 3 ]. Tumor-infiltrating lymphocytes (TILs) play an important role in promoting host protection against cancer and facilitating tumor escape from immune destruction [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%